MUZAKKI TRUST ANALYSIS ABOUT AMIL ZAKAT - Souvya Fithrie; idel waldelmi; Afvan Aquino (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This study discusses Muzakki Trust Analysis Against Amil Zakat in University of Lancang Kuning. This research uses survey method on muzakki that exist in Unilak environment, using questioner, interview and analyzed with descriptive technique, Based on field data proves that the level of trust muzakki to amil zakat which is pointed by the yellow University of lancang kuning with an average of 3.6. Followed by several high item items among others muzaki believe in amil appointed in managing upz with score 3.7 and also muzakkii assess officer obedient in running religion. And the cause of zakat muzakki UPZ Unilak institutions that factor officers, services, distribution of zakat funds and Lack of level of socialization of the zakat management unit to muzakki.